2020
DOI: 10.1126/sciimmunol.abf3698
|View full text |Cite
|
Sign up to set email alerts
|

Discordant neutralizing antibody and T cell responses in asymptomatic and mild SARS-CoV-2 infection

Abstract: Understanding the nature of immunity following mild/asymptomatic infection with SARS-CoV-2 is crucial to controlling the pandemic. We analyzed T cell and neutralizing antibody responses in 136 healthcare workers (HCW) 16-18 weeks after United Kingdom lockdown, 76 of whom had mild/asymptomatic SARS-CoV-2 infection captured by serial sampling. Neutralizing antibodies (nAb) were present in 89% o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
218
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(255 citation statements)
references
References 61 publications
31
218
2
4
Order By: Relevance
“…By contrast, responses to FEC pools were comparable in magnitude to the cumulative SARS-CoV-2-specific T cell responses detected in the HIV negative donors, likely reflecting the lower CMV seropositivity in the HIV negative group compared to the HIV positive group (54.28% CMV seropositive versus 97.87% CMV seropositive, respectively) ( Fig.2d). In line with previous studies we observed a wide breadth and range of cumulative SARS-CoV-2 T cell frequencies, with over 90% of donors in each group showing a response ( Fig.2e, f) 30,[39][40] . However, the proportion of HIV positive and negative donors with T cell responses to individual SARS-CoV-2 pools within given ranges varied, with a higher percentage of HIV positive donors having low level responses (Fig.2g).…”
Section: Sars-cov-2 Multi-specific T Cell Responsessupporting
confidence: 92%
See 2 more Smart Citations
“…By contrast, responses to FEC pools were comparable in magnitude to the cumulative SARS-CoV-2-specific T cell responses detected in the HIV negative donors, likely reflecting the lower CMV seropositivity in the HIV negative group compared to the HIV positive group (54.28% CMV seropositive versus 97.87% CMV seropositive, respectively) ( Fig.2d). In line with previous studies we observed a wide breadth and range of cumulative SARS-CoV-2 T cell frequencies, with over 90% of donors in each group showing a response ( Fig.2e, f) 30,[39][40] . However, the proportion of HIV positive and negative donors with T cell responses to individual SARS-CoV-2 pools within given ranges varied, with a higher percentage of HIV positive donors having low level responses (Fig.2g).…”
Section: Sars-cov-2 Multi-specific T Cell Responsessupporting
confidence: 92%
“…These data suggest that, despite effective ART, incomplete immune reconstitution may potentially impact on the magnitude of T cell responses to SARS-CoV-2. Previous observations have demonstrated an association between SARS-CoV-2-specific T cells, age and gender, with T cell immunity to Spike increasing with age and male gender in some studies 30 . Despite an older age and male predominance in our HIV cohort we did not detect any association between ELISpot responses to Spike and donor age ( Supplementary Fig.2f, g).…”
Section: Sars-cov-2 Multi-specific T Cell Responsesmentioning
confidence: 91%
See 1 more Smart Citation
“…We included a total of 169 blood RNA samples from 96 participants in a nested case-control study (Fig. S1) derived from an observational healthcare worker cohort (2628) . Of these, 114 samples (including 16 convalescent samples collected 6 months after infection) were obtained from 41 incident cases with SARS-CoV-2 infection, and 55 samples from uninfected controls.…”
Section: Resultsmentioning
confidence: 99%
“…Some of us have recently reported a UK HCW cohort in which about 10% of previously infected HCW carried very low or absent neutralizing antibody levels at 4-months and would presumably be vulnerable to reinfection. 37 Sekine et al described a potent memory T cell response, similar to those desirable in the context of successful vaccines and that confer long-term immunity, independent of the absence or presence of circulating antibodies. Approximately twice as many people showed T-cell immunity compared to those in which they detected antibodies.…”
Section: Discussionmentioning
confidence: 98%